MANAJEMEN SUMBER DAYA ANGGARAN KEUANGAN PENDIDIKAN - Choiriyah, Ngismatul (LP2M IAIN Palangka Raya, 2014)
Management education financing are all activities related to the planning, the use (execution) and accountability of funding education in schools or educational institutions.In general, existing activities in management education funding includes (1) Budget planning (budgeting), which is coordinating the activities of all the resources available to achieve the desired goals systematically. (2) Implementation (implenmentation involves accounting), namely the use of funds based on plans that have been made. (3) evaluation or accountability (auditing), namely the assessment of the implementation of the program that was created for the achievement of objectives.General principles of financial management of education are as follows: frugal, focused, open, thorough and periodic or transparent, accountable, effective and efficient. As for the types of funding that by its nature can be classified into two, among others: are routine funding, funding that is not routine. Meanwhile in other references on the types of budgets in education funding can be classified that the budget item by item budget programs, budgetary zero-based.Accountability is the process of proving and determining that what is being implemented in accordance with what was planned, this includes accountability receipt of funds, deposit and disbursement of funds in accordance with the planning (proportional)